The foreman discovers motion study [motion picture] (United States University Extension, University of California, 1954)
An introduction to the field of motion study and the simplifying of work. Shows, through a story situation, the experience of a typical foreman who comes in contact with motion study for the first time.
Keywords: Motion study; Research, Industrial